JUSTIFICATION OF THE COMPLEX TREATMENT OF PURULOUS COMPLICATIONS OF FOOT INJURIES IN PATIENTS WITH DIABETES MELLITUS - Golovakha, Maxim; Klyatsky, Yurii; Kozhemyaka, Maxim; Maslennikov, Serhii; Kosylo, Vasyl (Eastern Ukrainian Medical Journal, 2024)
In recent years, despite the development of modern methods of diagnosis and treatment of foot injuries in patients with diabetes mellitus, there has been an increase in the number of purulent-necrotic complications with a significant percentage of generalization of the infection. Due to potentially "catastrophic" wound healing, uncontrolled, irrational use of antibiotics, lack of regular blood glucose control, implementation of long and complex surgical interventions leads to the development of complications, including infection.The aim of the study. To substantiate the expediency of using a complex treatment scheme for purulent complications of foot bone fractures in patients with diabetes.Materials and methods. The results of treatment of 25 diabetic patients with foot injuries complicated by a purulent process were analyzed. In order to restore homeostasis disorders, patients received a complex of medical measures, including surgical treatment, infusion therapy, immunotherapy, antibiotic therapy. Patients were under the constant control of an endocrinologist.The results. As a result of complex treatment of patients, the inflammatory process was stopped in 21 (84%) patients, however, in 1 (4%) patient with stage 3 diabetic foot syndrome and in 3 (12%) patients with stage 4 according to the F.W.Wagner classification, the inflammatory process spread on the shin, therefore amputation was performed in this patients. The use of the developed treatment tactics, which included drainage of the wound with the removal of destroyed bone fragments, fixators (pins, screws, plates) in the maximum possible volume is the most effective method of surgical treatment of patients with this form of inflammation and allows you to save the foot, avoid the progression of purulent process and repeated surgical intervention.